Does ease-of-use contributes to the perception of enjoyment? A case of gamification in e-banking - Rodrigues, L. F.; Oliveira, A.; Costa, C. J. (Computers in Human Behavior, 2016)
The success of online games encouraged the development of gamification software in e-banking. Beside the growing trend of gamification, it is important understand how bank customers face the gamified applications, particularly as enjoyment and ease-of-use. To assess the determinants that influence the adoption of gamification in e-banking, we developed a research to propose a conceptual model that illustrates the adoption of gamified business applications by bank customers, in e-banking context. We conducted two quantitative studies (A and B) to understand how bank customers represent a gamified business software and its changes (or improvements) over time. Study A was performed in 2012 (N = 183), and study B in 2015 (N = 219). Online bank customers were invited to rate the importance of variables related to: socialness, ease-of-use, usefulness, enjoyment and intention to use e-banking systems with game features and social cues. The results show that ease-of-use and enjoyment are interrelated, and both have influence in e-banking usage. This study present theoretical ground of the conceptual model, and discuss two empirical studies, aiming to analyse the ease-of-use and enjoyment influence on bank customers. These findings will contribute directly to explain of adoption hedonic business software in e-banking